Effect of footwear longitudinal bending stiffness on energy cost, biomechanics, and fatigue during a treadmill half-marathon - Perrin, T. P.; Gerey, R.; Morio, C. Y. M.; Feasson, L.; Kerhervé, H. A.; Rossi, J.; Millet, G. Y. (Medicine & Science in Sports & Exercise, 2025)
Introduction Carbon plates have been used to increase running shoes` longitudinal bending stiffness (LBS), but their effect during a long duration run remains unknown. Our study aimed to identify the effect of LBS on energy cost of running (Cr), biomechanics, and fatigue during a half-marathon.